Assessing the efficacy of using mobile kraal-based manure fertilisation to improve sorghum productivity in semi-arid Zimbabwe - Moyo, Martin; Dube, Farayi; Magaisa, Alec; Riar, Amritbir (International Crops Research Institute for the Semi-Arid Tropics, 2025)
This study evaluated mobile kraaling, where cattle are penned directly in crop fields compared to tradition manuring and Pfumvudza (a conservation agriculture technology involving use of mulch, manure, mineral fertiliser). The study was conducted in 4 districts of Zimbabwe within an Action Research framework for three season (2022 -2025). In the initial phase five treatments (Mobile Kraaling, Mobile Kraaling + Pfumvudza, Pfumvudza, Traditional Manuring and Control) were tested with treatment refinement happening in subsequent season adding seven more treatments. Mobile kraals significantly increased yield (2,468 kg/ha) compared with traditional manuring (1,532 kg/ha), and the Mobile kraals + Pfumvudza produced the highest yield (3,636 kg/ha), outperforming Pfumvudza alone (2,950 kg/ha) and the control (895 kg/ha). Combining mobile kraaling with top-dressing further boosted yields by up to 600 kg/ha and top-dressing with nitrogen fertiliser alone improving yields even without organic inputs. Residual effects were evident, with previous-season kraaling yielding 1,757 kg/ha, increasing to 2,490 kg/ha when supplemented with nitrogen top dressing. Mulched Pfumvudza outperformed the Pfumvudza that was not mulched. PCA results for 16 soil parameters showed strong positive PC1 and PC2 scores for mobile kraal treatments, while traditional manure and control plots were consistently negative. Mobile kraaling also improved soil pH. Overall, Mobile kraals + Pfumvudza provided the most effective ISFM strategy.